(untitled) (Journal of the College of Basic Education, 2024)
he research included five chapters: Chapter one The first chapter included the research problem, its importance, objectives, hypotheses, limits, and definition of terminology The problem of the research was that the era in which we live is characterized by rapid change and renewal in accordance with the additions to knowledge, especially in teaching methods, and there are modern strategies found to improve the educational situation. It became clear to the researcher, through personal observation during implementation in schools and her continuous observation of the lessons, as well as reviewing the opinions of specialists and experts, that there is a weakness in the level of female students in learning basic volleyball skills and that their level does not rise to the required level, one of the reasons for which is the lack of use of diversity in modern and different methods and strategies. In teaching, including cooperative learning strategies and methods of scheduling exercises. Many teachers do not follow modern strategies and do not apply them in their practical lessons, and they rely on traditional methods that restrict the student’s personality and make his role negative in the learning process. Hence, the importance of research on using a cooperative learning strategy that enhances the student’s personality, makes him interact with the developments of the modern era, and helps him increase the ability to master concepts and general foundations that develop his abilities to solve problems and creativity, as well as improve his linguistic skills and ability to express, becomes clear. The research objectives included: Develop an educational curriculum using a cooperative learning strategy using the method of scheduling sequential and random exercises to learn some basic skills in volleyball. Identify the effectiveness of the educational curriculum using cooperative learning in light of the sequential method for learning some basic volleyball skills. Identify the effectiveness of the educational approach that uses cooperative learning in light of the random method to learn some basic volleyball skills. Identify which is more effective in the results of the post-tests for the two experimental groups and the control group.